CLINICAL PATHOPHYSIOLOGY OF CEREBRAL EDEMA (part 2) - A. A. Zadvornov; A. V. Golomidov; E. V. Grigoriev (Вестник анестезиологии и реаниматологии)
The article gives the updated understanding of the physiology of cerebral fluid exchange and pathophysiology of cerebral edema. The first part of the article has been devoted to a description of the mechanisms of fluid and electrolyte exchange in health and the second part describes pathophysiological aspects of cerebral edema development, going through certain stages. A cytotoxic edema is the first stage when fluid is redistributed between spaces. It is followed by the sodium deficiency in the interstitium resulting in the development of the second stage - an ionic edema characterized only by functional disorders of hematoencephalic barrier. The consequent anatomic disorder of hematoencephalic barrier results in the development of a vasogenic edema and transfer to the stage of hemorrhagic transformation. Understanding the mechanism of the brain edema development provides new prospectives of the management of this state.